Molecular genetic diversity analysis using SSR markers of basmati rice (Oryza sativa L.) genotypes of northern hill region, India - Dwivedi, Aparajita; Rathour, Rajeev; Basandrai, Daisy; Sarial, Ashok Kumar (Journal of Cereal Research, 2019)
The genetic diversity of 30 rice accessions both of basmati and non-basmati including 2 red rices collected from Rice and Wheat Research Centre, Malan was performed on the basis of 36 genome wide SSR markers with the objectives to quantify the genetic divergence and to identify the potential accessions. Molecular characterization grouped them according to their varietal affiliations into five major clusters. Majority of basmati genotypes were clustered together. SSR markers detected a total of 83 alleles ranging from 2-4. The pairwise genetic similarity values among different genotypes ranged from 0.17 to 0.92 with an average of 0.48 indicating the presence of moderate genetic diversity among the genotypes analysed. The PIC values reflected the level of diversity and allelic frequency among the varieties which varied widely among SSR loci from 0.062 to 0.664. Two SSR markers namely, RM7173 and RM101 were identified as genotype specific, for genotype HPR 2761 and Vasumati, respectively. Two advanced breeding lines of basmati HPR 2852 and HPR 2855 were clustered together with their basmati parents in dendrogram indicating maximum recovery of basmati genotypes. The polymorphism detected among the genotypes will be helpful in selecting genetically diverse parents in the future breeding programme. The information generated will be used for advanced studies in germplasm, pureline selection and rice breeding in the future breeding programme.DOI:http://doi.org/10.25174/2249-4065/2019/95583